Answer: x = 12
Explanation:
First you must simplify:
x + (x + 4) = 28
Reorder the terms:
x + (4 + x) = 28
Remove parenthesis around (4 + x):
x + 4 + x = 28
Reorder the terms:
4 + x + x = 28
Combine like terms: x + x = 2x
4 + 2x = 28
Solving
4 + 2x = 28
Now we must solve for the variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + 2x = 28 + -4
Combine like terms: 4 + -4 = 0
0 + 2x = 28 + -4
2x = 28 + -4
Combine like terms: 28 + -4 = 24
2x = 24
Divide each side by '2'.
x = 12
Simplifying
x = 12
Hope this helps! :)